Understanding intramembrane proteolysis: from protein dynamics to reaction kinetics - Langosch, Dieter; Scharnagl, C.; Steiner, H.; Lemberg, Marius (Trends in biochemical sciences, 2015)
Intramembrane proteolysis - cleavage of proteins within the plane of a membrane - is a widespread phenomenon that can contribute to the functional activation of substrates and is involved in several diseases. Although different families of intramembrane proteases have been discovered and characterized, we currently do not know how these enzymes discriminate between substrates and non-substrates, how site-specific cleavage is achieved, or which factors determine the rate of proteolysis. Focusing on γ-secretase and rhomboid proteases, we argue that answers to these questions may emerge from connecting experimental readouts, such as reaction kinetics and the determination of cleavage sites, to the structures and the conformational dynamics of substrates and enzymes.